KAMPUNG KREATIF JAGOI BABANG SEBAGAI UPAYA MEMAKSIMALKAN POTENSI DAERAH PERBATASAN - Sabinus Beni; Blasius Manggu; Yosua Damas Sadewo (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2021)
Jagoi Babang Creative Village is a border area between Bengkayang Regency, West Kalimantan Province, Indonesia with Serikin Malaysia, Sarawak Section as an official forum for Jagoi Babang border residents in developing Creative Industries, especially Handicrafts with basic ingredients of Rattan and Kapuak Bark with the characteristics of Dayak Bidayuh. In maximizing the existence of this Creative Village, of course, it will be faced with several things, therefore it is important to do research. The purpose of this study is to describe some of the challenges and opportunities that can become business opportunities for the younger generation, especially at the Jagoi Babang and Bengkayang borders in general. The research method uses qualitative methods with data collection techniques through in-depth interviews with traditional elders, community leaders and creative economy actors in the Jagoi Babang creative village. The results showed that, The challenges: Rattan raw materials are not available because the community does not cultivate rattan and only relies on the generosity of nature and the loss of forest replaced by oil palm plantations, the absence of marketing places and government efforts to overcome the prices of craftsmen, do not have patent rights which can be detrimental to splint craftsmen. Opportunities: Prices can be controlled by Indonesia, especially craftsmen, opportunities for investors to open rattan plantations and open new jobs, apply for patents that make it a characteristic of Bengkayang Regency and export rattan products typical of Dayak Bidayuh abroad. The conclusion from the results of this study is that there are still very open business opportunities with the establishment of the Creative Village to improve people's living standards and can provide new jobs and participation between the community and the Bengkayang district government. Keywords: Creative Village, Rattan, Border